Theoretical Investigation of Ferromagnetism and Optical Properties of CuCr2X4 (X = S, Se) Spinels via Ab-initio Calculations - Mahmood, Qasim; Alzahrani, Jameelah; Ghrib, T. (Journal of Materials and Physical Sciences, 2022)
The spintronics technology improve the spin functionality which captivated the existence of ferromagnetism. The control of magnetic properties by electrons spin and transport effect have been illustrated in CuCr2X4 (X = S, Se) spinels DFT through Wien2k and BoltztraP codes. The negative formation of energy established the thermodynamic stability of the examined spinels. The half metallic ferromagnetism in the analyzed spinel’s assures density of states. Magnetic moment (Integer value) and the insulating nature with down spin is the reaction of 100% spin polarization. The negative attainment of the condition have presented the prevailing part of electrons spin to create ferromagnetism.